The 13th IEEE International Symposium on Personal, Indoor and Mobile Radio Communications
DOI: 10.1109/pimrc.2002.1047352
|View full text |Cite
|
Sign up to set email alerts
|

2 GHz outdoor to indoor propagation at high elevation angles

Abstract: The case of outdoor to indoor propagation prediction at high elevation angles has been scarcely addressed and no direct relationship between the elevation angles and the building penetration loss has been reported.High Altitude Platform Stations -a new means of providing International Mobile Telephony (IMT-2000)-will be operating at high elevation angles. This paper examines the impact of the high elevation angles in the propagation mechanism and the penetration into buildings loss. A 3-D ray-tracing tool was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Relative permittivity Conductivity (S/m) Brick wall [7] 5.05 -5.52 0.01 Wood [6] 3.00 0.00 Formic [8] 5.00 0.00…”
Section: Methodsmentioning
confidence: 99%
“…Relative permittivity Conductivity (S/m) Brick wall [7] 5.05 -5.52 0.01 Wood [6] 3.00 0.00 Formic [8] 5.00 0.00…”
Section: Methodsmentioning
confidence: 99%
“…Relative permittivity Conductivity (S/m) Brick walls [6] 1.95 -6.95 0.0001 Tree Trunks [6] 2.75 -3.8 0.0001…”
Section: Methodsmentioning
confidence: 99%
“…This model applies to scenarios where the coverage of urban/suburban areas is achieved at elevation angles ranging between 55-90 degrees and the HAP is positioned above the city center. In [8], the authors studied the impact of high elevation angles in the propagation mechanisms; it was shown that in urban coverage scenarios by HAPs most of the buildings have at least one of the walls and the rooftop directly illuminated.…”
Section: Introductionmentioning
confidence: 99%